search points attachment profile arrow left arrow right star heart verified symbols equation arrow-down question mark check menu accountancyadministrationagriculturalalgebraallarabicartart_musicbelarusbelarus_altbiologybusinesscatalachemistrychineseeconomicsegzamenglishentrepreneurshipenvironmentethicseuskarafirst_aidfrenchgalegogeographygeologygeometrygermangrammarhealthhistoryindia_langindonesian_langinformaticsitalianjapanesekazachkazach_altkoreanlanguagelatinlawlife_scienceliteraturelogicmathematicsmusicnigerian_langother_languagesotherspedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligionrpa_langrussianrussian_altsciencesecurityskillssocial_sciencesociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation accountancyadministrationagriculturalalgebraall_1arabicartart_music_2belarusbelarus_altbiologybusiness_2catalachemistry_1chineseeconomicsexam_3englishentrepreneurshipenvironment_2ethicseuskarasecurity_1frenchgalegogeography_4geology_4geometrygermangrammarhealthhistoryindia-langindonesian-langinformaticsitalianjapanesekazachAsset 230koreanlanguagelatinlawlife-scienceliteraturelogic_2mathematicsmusicnigerian-langotherlanguagesother_1pedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligion_1rpa-langrussianrussian_altsciencesecurity_3_mskills_1allsocial_science_5_msociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation

Ответ

Проверено экспертом

Ответ дан
Timur128

(x -2)(x-3)= x(x+1)​

x²-3x-2x+6=x²+x

x²-x²-6x=-6

-6x=-6

x=1

Ответ: x=1

Ответ

Проверено экспертом

Ответ дан
denisstretyakov

displaystyle tt (x-2)(x-3)=x(x+1)\displaystyle tt x^2-3x-2x+6=x^2+x\displaystyle tt -3x-2x+6=x\displaystyle tt -5x+6=x\displaystyle tt -5x-x=-6\displaystyle tt -6x=-6\displaystyle tt x=frac{-6}{-6}\displaystyle tt underline{bold{x=1}}

Ответы и объяснения

Не тот ответ, который тебе нужен?